2001
DOI: 10.1039/b007283o
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the nonlinear dynamics of a direct methanol fuel cell

Abstract: This paper is related to the analysis of the dynamic behaviour of a liquid-feed direct methanol fuel cell (DMFC) under different operating conditions, based on an isothermal model accounting for the mass balances the charge balances, the reaction micro-kinetics and the mass transport phenomena. Conceptually, the fuel cell system is decomposed into its subsystems (anode and cathode compartments, diffusion layers, catalyst layers on both electrodes, proton exchange membrane (PEM)). The models of the subsystems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 11 publications
0
51
0
Order By: Relevance
“…10. During experiments it was found that a pulsed periodic methanol feeding strategy can result in a significant cell voltage increase [41,42]. Simulations show the same behavior.…”
Section: Modeling and Simulation Of The Dmfc System: Design And Analysismentioning
confidence: 64%
See 2 more Smart Citations
“…10. During experiments it was found that a pulsed periodic methanol feeding strategy can result in a significant cell voltage increase [41,42]. Simulations show the same behavior.…”
Section: Modeling and Simulation Of The Dmfc System: Design And Analysismentioning
confidence: 64%
“…. Possible reaction mechanism for the electrochemical methanol oxidation and corresponding rate equations, adopted from [41].…”
Section: Anodic Methanol Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies of Scott, Sundmacher and colleagues [9][10][11][12], a frequently used volumetric flow rate with the cells presented in [9] is 1.36 ml/min. This corresponds to a very low Reynolds number of Re = 1.32 inside the channels (details and comparisons see [5]).…”
Section: Volumetric Flow Ratesmentioning
confidence: 99%
“…Several investigations have focused on the direct methanol fuel cell, and have shown that the performance of the cell is strongly affected by methanol crossover from the anode to the cathode compartment [1][2][3][4]. This phenomenon is accompanied by a reduction in cell voltage, which depends on experimental parameters such as fuel concentration, applied current density, stoichiometric factor and temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%